2019
DOI: 10.3390/app9071482
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lipid and Water Contents by Time-domain Diffuse Optical Spectroscopy and Dual-energy Computed Tomography in Breast Cancer Patients

Abstract: We previously compared time-domain diffuse optical spectroscopy (TD-DOS) with magnetic resonance imaging (MRI) using various water/lipid phantoms. However, it is difficult to conduct similar comparisons in the breast, because of measurement differences due to modality-dependent differences in posture. Dual-energy computed tomography (DECT) examination is performed in the same supine position as a TD-DOS measurement. Therefore, we first verified the accuracy of the measured fat fraction of fibroglandular tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In addition to greater penetration depth, NIR spectroscopy provides more quantitative parameters because of the light absorption by lipid and water at higher wavelengths. A study by Ohmae et al in breast cancer patients, has shown such optical measurements of lipids and water to be highly concordant with computed tomographic measurements [43] . Tromberg et al have used a combination of hemoglobin and lipid absorption as well as scattering to determine a “Tissue optical index” for predicting treatment response in breast cancer patients undergoing neoadjuvant chemotherapy [44] .…”
Section: Discussionmentioning
confidence: 88%
“…In addition to greater penetration depth, NIR spectroscopy provides more quantitative parameters because of the light absorption by lipid and water at higher wavelengths. A study by Ohmae et al in breast cancer patients, has shown such optical measurements of lipids and water to be highly concordant with computed tomographic measurements [43] . Tromberg et al have used a combination of hemoglobin and lipid absorption as well as scattering to determine a “Tissue optical index” for predicting treatment response in breast cancer patients undergoing neoadjuvant chemotherapy [44] .…”
Section: Discussionmentioning
confidence: 88%
“…Optical methods based on the difference in the scattering and absorption properties of normal and tumor tissues have been actively developed for diagnosis [ 19 , 20 ] and monitoring of breast pathology [ 21 24 ] . Diffuse optical spectroscopy imaging (DOSI) utilizes light of far-red and near-infrared spectral range (~ 650 to 1000 nm), which has a low attenuation rate in tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These eLEDs emit light at selectable wavelengths in the near-infrared region, including 690, 750, 800, and 850 nm [11]. The choice of these wavelengths is based on the variations in extinction coefficients among primary constituents in breast tissue, such as oxyhemoglobin (HbO2), deoxyhemoglobin (Hb), fat, and water (H2O) [21], [22]. Previous research has demonstrated that the absorption coefficients of these components are wavelength-dependent [4].…”
Section: Optiscan Probe and Imaging Processmentioning
confidence: 99%